Financialization, common stochastic trends, and commodity prices - Moses M. Kupabado; Juergen Kaehler (Journal of Futures Markets, 2021)
Commodity financialization has been a subject of discussion since the 2008 financial crisis. It is estimated that between 2003 and 2008, index investors' positions increased from 13 billion to 317 billion. Surprisingly, most studies, predominantly based on Granger-causality testing, find no relationship between financialization and commodity prices. We examine the effects of shocks to the common stochastic trends in the index positions, the spot and futures prices of Chicago corn and soybeans, WTI crude oil and Henry Hub natural gas. The results show that financialization has contributed to the price movements of these commodities.
Keywords: 330; commodities; common trends; financialization; futures prices; index investors; spot prices